Introductory Trial of Tropical Pines in Andaman Islands A Nursery Study - Sharma, S. K. (Indian Forester, 1975)
Attempts at raising quick growing tropical pines in the Andamans were started in the year 1969. A chronological account of nursery trials conducted so far is given in this article for a comparative study of the performance of various tropical pines tried in these Islands. The results so far obtained point to the most promising of the tropical pines raised and the best nursery technique to be adopted in the climatic conditions obtained in these Islands.